Pengaruh Implementasi Program Adiwiyata Terhadap Perilaku Warga Sekolah Pada SekolahAdiwiyata Mandiri Di Kota Pekanbaru - Lusiana Sri Sunarti; Isjoni Isjoni; Zulkarnaini Zulkarnaini (Universitas Riau, 2017)
This research was conducted from February to April 2017 and took place in SMAN 1 and SMAN 8 Kota Pekanbaru to analyzing the influence simultaneously and partially, directly and indirectly between environmentally sound policy variables, environment based curriculum, participatory environment based activities and management of environmentally friendly support facilities On the behavior of school residents, the influence of school residents' behavior on environmental awareness, the availability of oxygen for school residents by conducting observations, surveys, interviews and documentation. Based on the results of the study, simultaneously affect 36.5%. Partially there is no influence between environmentally sound policy, and environment-based curriculum on the behavior of school citizens. Meanwhile, participatory environment based activities and management of environmentally friendly supporting facilities have a significant, direct and indirect effect on the behavior of school residents. The behavior of school residents has no significant effect on environmental awareness. The availability of oxygen based on the number of trees has been met for all school residents.